Women in Between: Gender, Refugee Experience and Ageing - Havelková, Hana; Ezzeddine, Petra (Lidé města, 2016)
The study is based on interviews with women with refugee experience from the former Yugoslavia, aged 50+, who have already been living in the Czech Republic for more than twenty years. It covers a long time period of life in migration, which has allowed us to show that the refugee experience of women is not linear but cyclical, gaining new significances at various stages of women’s lives, in various social contexts and transnational environments. There is a special focus on ageing and entrance into retirement age, when the women find themselves under a double pressure: they are trying to safeguard their own vulnerable position at work and at the same time to meet the normative commitments (traditionally expected from women) regarding transnational care of seniors. The study looks at migration from an intersectional perspective in investigating how gender, age, ethnicity, migration status and social class of the women we studied formed their life in the new society.